2002
DOI: 10.1211/002235702760345536
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent vasorelaxation induced by L-carnitine in isolated aorta from normotensive and hypertensive rats

Abstract: The aim of this work was to investigate the mechanism of the vasodilatory effect induced by Lcarnitine. Relaxation produced by L-carnitine was studied in rat aortic rings with and without functional endothelium, pre-contracted with phenylephrine by adding cumulative doses of Lcarnitine (10 7 to 10 3 M). The relaxation evoked by L-carnitine reached higher values in aortic rings from spontaneously hypertensive rats than those obtained in arteries from normotensive rats; no relaxation was produced in de-endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
1
12
0
3
Order By: Relevance
“…Nitric oxide production in the aorta of hypertensive rats is enhanced by L-carnitine through PI3 and Akt kinases [35], and PLC promotes prostaglandin synthesis in subcutaneous arteries in humans [20]. We showed that the antioxidant and anti-inflammatory properties of L-carnitine protected RTCs from carboplatin-mediated injury.…”
Section: Discussionmentioning
confidence: 78%
“…Nitric oxide production in the aorta of hypertensive rats is enhanced by L-carnitine through PI3 and Akt kinases [35], and PLC promotes prostaglandin synthesis in subcutaneous arteries in humans [20]. We showed that the antioxidant and anti-inflammatory properties of L-carnitine protected RTCs from carboplatin-mediated injury.…”
Section: Discussionmentioning
confidence: 78%
“…L-carnitine and its derivatives are known to have vasodilating properties which might be related to increased prostaglandin synthesis [22]. Both L-carnitine and propionyl-L-carnitine were previously reported to restore endothelium-dependent relaxation at reperfusion in experimental setting [23], with an action on the thromboxane A 2 /prostaglandin H 2 receptor being a possible mechanism involved [24]. All these observations highlight the importance of vascular mechanisms in the effect of carnitine derivatives.…”
Section: Discussionmentioning
confidence: 92%
“…Both LC and PLC are able to induce endothelium-dependent relaxation. The former enhances NO production in the aorta from hypertensive rats [1] and the latter promotes prostaglandin synthesis in subcutaneous human arteries [2]. Furthermore, we have recently reported that both compounds improved endothelial dysfunction in aortic rings from spontaneously hypertensive rats (SHR) by increasing NO participation in endothelium-dependent relaxations.…”
Section: Introductionmentioning
confidence: 99%